Ruídos em sistema de freio a disco: correlação da análise de autovalores complexos com métodos experimentais - Claudio Júnior Ferreto (2018)
As vehicle quality improves, customers demand quieter brakes. Customer complaints result in significant warranty costs, motivating the need to study brake noise in the early stages of the project. During brake operation, the friction between the brake pads and the disc can induce a dynamic instability in the system. This instability can radiate noise, commonly known as brake squeal. Automotive disc brake squeal has been a challenging issue for many engineers and researchers due to its immense complexity. This dynamic instability is linked to an unstable vibrating mode of the system. This mode can be identified during complex eigenvalue extraction because the real part of the eigenvalue corresponding to an unstable mode is positive. This finite element method (FEM), which is known as Complex Eigenvalue Analysis (CEA), can also be used to interpret test results, simulate changes in geometry or material properties, and explore innovative ideas. The purpose of this work is to investigate the correlation of this numerical method with experimental results. In addition to that, a geometry change is proposed in the model in order to eliminate an unstable mode. At the end, the effectiveness of this modification is evaluated with a brake noise dynamometer test. The maximum variation between damped natural frequency of the unstable eigenvalue and the squeal frequency was 2,4%. This result shows a strong correlation between the finite element model and the experimental tests, proving that this approach can be applied to the design of disc brake systems. However, the amount of unstable modes predicted in the model is overestimated and requires at least one experimental test in dyno or in vehicle in order to confirm which of the eigenvalues with positive real part will actually be excited under the operational conditions of the brake system.